Success Factors for Implementing Learning Design : Final Report. - Dalziel, James (Office for Learning and Teaching, 2014)
Final report of a Teaching Fellowship at Macquarie University. The Fellowship provided an opportunity for a series of meetings with international experts to develop a new conceptual model for the future of Learning Design, named The Larnaca Declaration on Learning Design. This model provides guidance for implementing Learning Design to improve teaching and learning in higher education, including discussion of how Learning Design contributes to related areas such as graduate attributes, curriculum planning, the use of technology in education and massive open online courses (MOOCs). The Larnaca Declaration has subsequently become a focal point for discussion in the field of Learning Design.